2016
DOI: 10.1371/journal.pone.0157937
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Analysis of Genes Associated with Autism Spectrum Disorders Reveals Differential Evolutionary Constraints

Abstract: The burden of comorbidity in Autism Spectrum Disorder (ASD) is substantial. The symptoms of autism overlap with many other human conditions, reflecting common molecular pathologies suggesting that cross-disorder analysis will help prioritize autism gene candidates. Genes in the intersection between autism and related conditions may represent nonspecific indicators of dysregulation while genes unique to autism may play a more causal role. Thorough literature review allowed us to extract 125 ICD-9 codes comorbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 39 publications
0
17
1
1
Order By: Relevance
“…Of the five clusters, cluster 1 consisted of all persons who responded to vitamin B6. Although we could not identify meaningful characteristics of the other four clusters (clusters 2 to 5), the AP analysis suggested that persons with ASD may be highly heterogeneous, as previously reported 9 .…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Of the five clusters, cluster 1 consisted of all persons who responded to vitamin B6. Although we could not identify meaningful characteristics of the other four clusters (clusters 2 to 5), the AP analysis suggested that persons with ASD may be highly heterogeneous, as previously reported 9 .…”
Section: Discussioncontrasting
confidence: 65%
“…Previous attempts to evaluate the efficacy of vitamin B6 in treating persons with ASD have failed to produce consistent findings 4 8 . ASD is highly heterogeneous 9 , and identifying a subgroup of persons who may show responsiveness to vitamin B6, if any, is important.…”
Section: Introductionmentioning
confidence: 99%
“…As most clinical cases are associated with a broad spectrum of developmental delay and autistic features, it is also critical to apply a comprehensive genetic analysis approach to increase performance and diagnostic yield. One of the main reasons for the unfeasibility of the genetic panels for ASD is because of the variety of genetic profiles and phenotype diversity in the spectrum, contributing to the popularization of WES and WGS (26). WGS is an ideal option to analyze ASD genotypical variety and complexity, not only due to the possibility of investigating the important regulatory intergenic region (27, 28), but also because of improved sequence coverage comparing to WES low coverage regions affecting essential ASD-related genes (16, 29, 30).…”
Section: Tools For Unveiling the Genetic Of Autism Spectrum Disordermentioning
confidence: 99%
“…Importantly, there are many metabolic and regulatory pathways underlying autism, some of which seem unique to this condition (David et al, 2016a). The quest to discover causality relations, including the necessary and sufficient conditions, is difficult.…”
Section: Epilepsymentioning
confidence: 99%